The Result of Conveying a Model Integrating Buddhist Teachings and Resilience Quotient to Prevent Victimization by Pseudo-science in Thai Society - Phookonglee, Asst.Sudjai; Kinasen, Assist.Prof.Dr.Winyu (Journal of Dhamma for Life, 2024)
The aim of this research was to convey a model that integrated Buddhist teachings and resilience concepts to counter pseudo-scientific beliefs in Thai society. The research employed 30 carefully selected participants, based on specific criteria, assessed the effectiveness of the integrated model. Research tools were a model integrating Buddhist teachings and resilience quotient to prevent victimization by pseudo-scientific in Thai society validated by six experts in focus group discussion, and assessments of mental resilience and validated by five experts. Statistics used in this research included mean, standard deviation, and Paired Sample t-tests. The results of conveying FSS Model interventions significantly improved overall resilience scores (before intervention: = 2.74, P = .00; after the intervention: = 3.83, P = .00), demonstrating a positive impact. In conclusion, the integration of Buddhist teachings and resilience principles appears promising in protecting individuals from falling victims to pseudo-scientific beliefs in Thailand, particularly when applied in educational monastic centers.